Paleobiodiversidade de vertebrados pleistocênicos da localidade Sanga dos Borba, Pântano Grande, Rio Grande do Sul - Silva, Yan Eduardo da (2022)
Herein we describe a new record of Pleistocene megafauna (Mammalia and Testudines), for the locality of Sanga dos Borba, municipality of Pântano Grande, Rio Grande do Sul state, southern Brazil. An OSL age was performed for the fossiliferous level, corresponding to 98,920±17,750 years BP. This is the oldest outcrop for the continental Pleistocene in Rio Grande do Sul so far. The presence of Testudines is based on three morphotypes, using the size to separate in large, medium and small Chelonia. The record of large size Testudines were compared with occurrences in the Pampean region in Argentina and Uruguay.